PENGARUH UDARA MASUK TERHADAP SUHU AIR CONDITIONER (AC) KAPASITAS 1 PK PADA RUANG INSTALASI UJI - ., Lagiyono; Luthfianto, Saufik; Riyadi, Dani (ENGINEERING, 2011)
Engine coolant is a tool used something, like room, food, medicine, and others. The aim the research conducted in this thesis is to determine whether there is influence of temperature contitionedair intake capacity of 1 PK and how much effect. This study used test installation of air conditioner brand CHANGHONG 1PK capacity by varyinng the inlet air using an electric blower with 4 calculation, ie 1 minute, 2 minute, 3 minute and 4 minute of data taken by measuring devices include: thermocouples, termolaser, preasure gauge, stop watch, an electric blower and pliers amperes, instead madde room cabin which has a length of 150 cm, width 100 cm tall with a normal temperature of 16ºC to achieve steady. After steady (moving and temperature gauge on the space and equipment) are data taken at each use of the fan. The research data obtained were analyzed dy using the characteristic table refrigerant R-22 to get the price preasure and enthalpy on each fan. Enthalpy is used to find the value of cooling rate on the characteristics of each of the incoming air every minute. Test conducted to get the results for 1 minute mref = -0,4997 kg/s, Qe =-0,3994 kW, Qc =3,3310 kW, RE = -6,666 kJ/kg, COP = 3,9844. Whitin 2 minutemref = -2,2558 kg/s Qe =3,2449kW, Qc = 2,4373kW, RE = -9,339 kJ/kg, COP = 1,3997. Whiten 3 minute mref = 2,2717 kg/s Qe =2,1351kW, Qc = 1,7051kW, RE = -6,666 kJ/kg, COP = 4,3398. As for time of 4 minute mref = -0,4997 kg/s Qe =4,16699kW, Qc = 3,3310kW, RE = -6,666 kJ/kg, COP = 3,9844. From the results of research conducted for Changhong air conditioner with a capacity of 1 PK temperture chenges every time.Keyword : Refrigeran 22, Capacity Evaporator, Condenser Capacity, Refrigeration Effect, Air Conditioner.